PERBANDINGAN TINGKAT VOLUME PENJUALAN SERTA PROFITABILITAS SEBELUM DAN SESUDAH SERTIFIKASI HALAL (STUDI PADA PT. MARTINA BERTO TBK) - Finidiah Safariana; Alvien Nur Amalia (Ibs Press, 2023)
The aim of this study is to determine the comparison of sales volume and profitability of companies before and after getting halal certification. In this study the authors used the method of the event study approach, event windows and event date. Using the financial statements 5 years before halal certification and 5 years after halal certification, namely in 2007 to 2017. The results of the study by the author can be concluded that there are differences in sales volume and profitability after halal certification, sales volume has increased, while profitability remains not after halal certification.